2019
DOI: 10.1002/asna.201913561
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the number of X‐ray pulsars in IC 10 from a deep XMM‐Newton observation

Abstract: We report the most sensitive search yet for X-ray pulsars in the dwarf starburst galaxy IC 10, which is known to contain a population of young, high-mass X-ray binaries. We searched for pulsations in 207 point-like X-ray sources in the direction of IC 10 by a 2012 XMM-Newton observation with a total exposure time of 134.5 ks. Pulsation searches in faint objects can be sensitive to the energy bands of the light curves, as well as the source and background extraction areas. We analyzed separately the PN and meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…To confirm the nature of M33 X-8, we searched for pulsations in both NuSTAR epochs using Lomb-Scargle periodograms (the same method described in Yang et al 2017aYang et al , 2019a. We found that a periodic signal was independently detected in both telescopes FPMA (769.42 ± 4.87 s) and FPMB (724.82 ± 5.22 s) with 99% significance during the first NuSTAR epoch (ObsID 50310002001).…”
Section: M33 X-8mentioning
confidence: 95%
“…To confirm the nature of M33 X-8, we searched for pulsations in both NuSTAR epochs using Lomb-Scargle periodograms (the same method described in Yang et al 2017aYang et al , 2019a. We found that a periodic signal was independently detected in both telescopes FPMA (769.42 ± 4.87 s) and FPMB (724.82 ± 5.22 s) with 99% significance during the first NuSTAR epoch (ObsID 50310002001).…”
Section: M33 X-8mentioning
confidence: 95%
“…The X-ray Multi-Mirror Mission (XMM-Newton) observation in 2003 has the longest exposure time. We used the standard procedure (see [20][21][22][23][24]) to extract the source. The folded light curve shows two double peaks and double troughs.…”
Section: Light Curves and Spectramentioning
confidence: 99%
“…Extensive studies of X-ray variability in the SMC sample have been performed (e.g., Laycock et al 2005;Eger & Haberl 2008;Galache et al 2008;Haberl & Sturm 2016;Lazzarini et al 2019;Haberl et al 2022). HMXBs have also been studied in the Large Magellanic Cloud (LMC; Lang et al 1998;Coe et al 2015b;Antoniou & Zezas 2016;van Jaarsveld et al 2018;Maitra et al 2023), the dwarf starburst galaxy IC 10 ( Massey et al 2007;Laycock et al 2017;Noori et al 2017;Yang et al 2019), the spiral galaxy NGC 300 (Kang et al 2016;Binder et al 2017), and M31 (Williams et al 2004;Lazzarini et al 2021).…”
Section: Introductionmentioning
confidence: 99%